2006
DOI: 10.1172/jci25811
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin action in the brain controls adipocyte metabolism

Abstract: Many homeostatic processes, including appetite and food intake, are controlled by neuroendocrine circuits involving the CNS. The CNS also directly regulates adipocyte metabolism, as we have shown here by examining central action of the orexigenic hormone ghrelin. Chronic central ghrelin infusion resulted in increases in the glucose utilization rate of white and brown adipose tissue without affecting skeletal muscle. In white adipocytes, mRNA expression of various fat storage-promoting enzymes such as lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
365
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(402 citation statements)
references
References 74 publications
31
365
1
4
Order By: Relevance
“…Expression of the key element in the fatty acid synthesis pathway SCD1 mRNA increased, but acetyl‐CoA carboxylase (ACC), fatty acid synthase (FAS), and carnitine palmitoyl transferase (CPT)‐1α mRNAs were unchanged in one study where ghrelin was administered (Theander‐Carrillo et al ., 2006). In another report, a low dose of ghrelin administered peripherally produced an increase in FAS and decreases in CPT‐1α mRNAs expression without affecting food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the key element in the fatty acid synthesis pathway SCD1 mRNA increased, but acetyl‐CoA carboxylase (ACC), fatty acid synthase (FAS), and carnitine palmitoyl transferase (CPT)‐1α mRNAs were unchanged in one study where ghrelin was administered (Theander‐Carrillo et al ., 2006). In another report, a low dose of ghrelin administered peripherally produced an increase in FAS and decreases in CPT‐1α mRNAs expression without affecting food intake.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that chronic stimulation of this receptor by ghrelin (Tschöp et al 2000) or by synthetic growth hormone secretagogues (Lall et al 2001) increases fat mass in rodents, by a mechanism that is independent of the hypothalamo-pituituary growth axis and, unexpectedly, did not appear to involve a hyperphagic response. Indeed, it has been proposed that ghrelin decreases fat utilization (Theander-Carrillo et al 2006;Tschöp et al 2000), implying that the CNS circuits mediating ghrelin's acute orexigenic effects differ, at least in part, from those involved in fat accumulation. We noticed previously that ghrelin's orexigenic effects decline after a few days of repeated peripheral ghrelin injection (Dornonville de la Cour et al 2005).…”
Section: The Central Ghrelin Signalling Systemmentioning
confidence: 99%
“…The adipogenic actions of ghrelin have also been suggested to be mediated directly by the regulation of peroxisome proliferator activated receptor γ (PPAR-γ) activity (Barazzoni et Thompson et al, 2004), although it has been suggested that ghrelin may also indirectly regulate peripheral adiposity through the hypothalamic melanocortin receptors and the efferent sympathetic nervous system independent of food intake (Nogueiras et al, 2007;Theander-Carrillo et al, 2006). These observations led to the proposal that ghrelin operates as a peripheral signal for energy insufficiency, whose levels rise in conditions of negative energy balance in order to activate homeostatic responses to keep stable the whole body energy balance (Tang-Christensen et al, 2004;Zigman and Elmquist, 2003).…”
Section: Page 8 Of 41mentioning
confidence: 99%